Isolation and Identification of Bacteria from Food Vendors (International Journal of Scientific Research and Management (IJSRM), 2024)
A fundamental need for food quality is food safety. This project aims to study bacteria associated with food vendors in hi-tech city public places street food vendors, Food such as Pani puri, Fried rice, chat, Shawarma waterleaf, spinach collected from street food vendors in a zip storage bag. 10 food samples were collected from food vendors. On the same day, isolation of bacteria was done from different food samples and the isolates from this study were found to be E. coli, Staphylococcus Aureus, Bacillus, Salmonella species, and Shigella species. Foods that contain several bacteria get transmitted due to use of tainted raw food components and particles, dirty water, unhygienic preparation methods, and infected containers all contributed to the contamination and unhygienic conditions, which may result in foodborne infections involving diseases that affect the cardiovascular, musculoskeletal, respiratory, and immune systems. Besides these, some beneficial bacteria stay in the intestine.